Exploration of Sepsis-Associated Coagulopathy Severity and Pediatric Septic Shock Outcomes - Loberger, Jeremy M.; Aban, Inmaculada B.; Prabhakaran, Priya (Journal of Pediatric Intensive Care, 2020)
The objective of this study was to explore correlations between sepsis-associated coagulopathy (SAC) in pediatric septic shock and clinical outcomes. This was a retrospective cohort study of all children admitted to a single, academic pediatric intensive care unit with septic shock over 6 years. The prevalence of SAC was 93.5% with 61% being severe. Those with severe SAC were more likely to have a positive blood culture and have longer median duration of ventilation. All observed mortalities occurred in the severe SAC and indeterminate SAC groups. SAC is highly prevalent in pediatric septic shock and may predict important outcomes.
Keywords: septic shock; disseminated intravascular coagulation; PICU